Chemical analysis of Murex-dyed textiles from wadi Murabba'at, Israel. (September 2015) - Sukenik, Naama; Varvak, Alexander; Amar, Zohar; Iluz, David
Abstract: In this article we shall focus on the chemical and chromatographic analyses that were used in the study of three textiles that were found in a cave in wadi Murabba'at, the Judean desert. The textiles date to the Roman period, and were dyed with a prestigious purple dye. High Performance Liquid Chromatography (HPLC) identified the Murex sea snail Hexaplex trunculus as a source of dye for the three textiles. Nevertheless, the dyeing process was not uniform. The color of one textile was modified to greenish-blue, apparently by exposure to the sun during the dyeing process. The two other textiles were subject to a double-dyeing process, and underwent a second dipping in a dye solution extracted from the Armenian cochineal insect. This process resulted in a reddish-purple color, which was indicative of high status. This is the first time that this dyeing technique was identified in ancient textiles from Israel. The multi-disciplinary research also identified different origins for the textiles. Highlights: Colors derived from Murex snail shell may range in hue from bluish-purple to reddish-purple, according to the dyeing process. MBI, MBIR, and DBI are compounds present only in mollusk dyes. Extracts of dyed fabrics were analyzed by means of HPLC. The three textiles from Murabba'at were dyed with Hexaplex trunculus sea mollusk. Two textiles underwent a double dyeing process using Hexaplex trunculus and Armenian Cochineal.